2011
DOI: 10.1523/jneurosci.1833-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Novel Regulation of Parkin Function through c-Abl-Mediated Tyrosine Phosphorylation: Implications for Parkinson's Disease

Abstract: Mutations in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
202
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(213 citation statements)
references
References 31 publications
8
202
3
Order By: Relevance
“…It has been reported that c-Abl mediates PD pathogenesis via targets such as parkin and α-synuclein. 9,10,16 However, the molecular mechanisms by which c-Abl participates in oxidative stress-induced PD remain unknown. Because c-Abl is a tyrosine kinase, its substrates can be determined via SILAC technology followed by the identification of the tyrosine-phosphorylated peptides.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that c-Abl mediates PD pathogenesis via targets such as parkin and α-synuclein. 9,10,16 However, the molecular mechanisms by which c-Abl participates in oxidative stress-induced PD remain unknown. Because c-Abl is a tyrosine kinase, its substrates can be determined via SILAC technology followed by the identification of the tyrosine-phosphorylated peptides.…”
Section: Resultsmentioning
confidence: 99%
“…25 Recently, extensive studies have been performed on c-Abl in the nervous system to investigate its role in neurodegenerative disease. [9][10][11][12][13][14]26 For example, c-Abl kinase has been reported to regulate the accumulation of AIMP2 (aminoacyl tRNA synthetase complex-interacting multifunctional protein 2), FBP1 (far upstream elementbinding protein 1), and α-synuclein in PD models. 9,10,11 Here, by using the SILAC analysis, we identified p38α as a major Figure 6 The p38α inhibitor SB203580 protects against MPTP-induced dopaminergic neuronal death and motor deficits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, proteasomal degradation by parkin-mediated Lys-48-linked substrate polyubiquitination has been the most extensively studied function of parkin. In particular, AIPM2 (aminoacyl-tRNA synthetase-interacting multifunctional protein type 2; p38/JTV-1) (15), FBP1 (fuse-binding protein 1) (16), and PARIS (17) have been found to accumulate in parkin knock-out mice, suggesting that parkin-mediated ubiquitination is required for their targeting to the 26 S proteasome for degradation. Recently, parkin activity has been associated with the clearance of depolarized mitochondria by mitophagy (18), where parkin recruitment to mitochondria and its ubiquitin ligase activity are controlled by PINK1 (PTENinduced putative kinase 1) phosphorylation of both parkin and Ub (19 -21).…”
mentioning
confidence: 99%